Feature issue introduction: biophotonic materials and applications - Lee, Kwang-Sup (Biomed Opt Express, 2016)
Biophotonics can be defined as the interplay of light and biological matter. The percolation of new optical technology into the realm of biology has literally shed new light into the inner workings of biological systems. This has revealed new applications for optics in biology. In a parallel trend, biomolecules have been investigated for their optical applications. Materials are playing a central role in the development of biophotonics. New materials, fabrication methods, and structures are enabling new biosensors, contrast agents, imaging strategies, and assay methods. Similarly, biologic materials themselves can be used in photonic devices. In this context, two open-access, rapid-publication journals from The Optical Society of America (OSA), Optical Materials Express and Biomedical Optics Express, will publish a joint feature issue covering advances in biophotonics materials.